Egypt beyond the Crisis : Medium-Term Challenges for Sustained Growth - Herrera, Santiago; Selim, Hoda; Youssef, Hoda; Zaki, Chahir (2012)
The paper analyzes the impact of the recent global crisis in the context of the previous two decades' growth and capital flows. Growth decomposition exercises show that Egyptian growth is driven mostly by capital accumulation. To estimate the share of labor in national income, the analysis adjusts the national accounts statistics to include the compensation of self-employed and non-paid family workers. Still, the share of labor, about 30 percent, is significantly lower than previously estimated. The authors estimate the output costs of the current crisis by comparing the output trajectory that would have prevailed without the crisis with the observed and revised gross domestic product projections for the medium term. The fall in private investment was the main driver of the output cost. Even if private investment recovers its pre-crisis levels, there is a permanent loss in gross domestic product per capita of about 2 percent with respect to the scenario without the crisis. The paper shows how the shock to investment is magnified due to the capital-intensive nature of the Egyptian economy: if the economy had the traditionally-used share of labor in income (40 percent), the output loss would have been reduced by half.